Species and Abundance of Sea Urchins (Diadematidae) on Different Environmental Pressure Conditions - Pratama Diffi Samuel; Dewa Gede Raka; Bagyo Yanuwiyadi (Journal of Tropical Life Science, 2017)
Genetic diversity of sea urchin are very high; there are no two organisms of the same species that are exactly alike. Dense aggregation of sea urchin is responsible for the destruction of marine algae communities on coral reef ecosystem. The purpose of this study is to identify the species and abundance of sea urchins at different environmental conditions, to analyze the influence of water conditions on the abundance of sea urchins and to analyze the role of sea urchin as water quality and abiotic environmental conditions bio-indicators. Data collection procedures carried out in three stage that are: assessment of the status of coral reefs, sea urchins sampling and analysis of data. Data condition of coral reefs is drawn using methods kick frequency. Urchin abundance data retrieval is done by timed swims or snorkeling and species of sea urchins seen through genetic approach, by DNA sequencing. Identify the types of sea urchins in this study conducted with the gene fragment sequences Cytochrome Oxidase subunit I (COI). Stages isolation of DNA-based procedures uses Gsync DNA Extraction Kit from Geneaid. The species that identify in this study is Diadema setosum. Location with high environmental pressures has a low quality of coral reef ecosystems and has a great abundance of sea urchins. This proves that the water environmental conditions greatly affect the abundance/density of sea urchins. In locations with relatively low environmental stress or a sheltered environment the abundance of sea urchins is low.